2018
DOI: 10.5935/medicalexpress.2018.mo.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac vagal index varies according to field position in male elite football players

Abstract: BACKGROUND: Cardiac vagal index (CVI) is supposedly higher in athletes and may differ between sports and/or between field positions. OBJECTIVE: To compare CVI: a) between elite football players vs. non-athletes and b) according to five football positions. METHOD: 242 football players of the first Brazilian/Angolan division were divided in five positions (N): goalkeepers (17), defenders (44), wingers (34), midfielders (87) and forwarders (60) and compared with 303 age-matched healthy non-athletes. CVI was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These findings have practical implications for soccer performance, as previous research has indicated that the highest scores in the cardiopulmonary system might be predictive of athletic performance enabling athletes to attack and defend more effectively as likewise as faster recuperation [11,21]. This is important because the endurance capacity of soccer players appears to be related to improvements in the level of play.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings have practical implications for soccer performance, as previous research has indicated that the highest scores in the cardiopulmonary system might be predictive of athletic performance enabling athletes to attack and defend more effectively as likewise as faster recuperation [11,21]. This is important because the endurance capacity of soccer players appears to be related to improvements in the level of play.…”
Section: Discussionmentioning
confidence: 70%
“…Bishop et al [19] states that a higher VO2max in soccer is an obligatory condition to prolong high-intensity displacements due to the greater contribution of aerobic metabolism to the performance of late sprinters. Position shared by several researchers [11,[20][21] who verify a faster recovery process in those with higher VO2max. Therefore, it can be seen in some studies on international sports teams that this physiological parameter ranged from 45.1 to 55.5 mL/kg/min [16,22].…”
Section: Discussionmentioning
confidence: 99%